Impact of Screening for Salivary Gland by Ultrasonography - Onda, Kanna (Yonago Acta Med, 2020)
BACKGROUND: Ultrasonography is superior to other imaging modalities for detecting salivary gland diseases. However, there have been no reports of the results of salivary gland screening with ultrasonography. In this study, the salivary glands were also observed during thyroid ultrasonography to determine the degree of salivary gland abnormalities detected by ultrasonography. METHODS: This study was conducted retrospectively using medical records. It assessed the association between the following abnormal findings detected during thyroid ultrasonography and their final diagnoses: atrophy/swelling, unclear demarcation from surrounding tissues, decreased salivary gland parenchyma echo level, heterogeneity of parenchyma, hypervascularity of salivary gland parenchyma, dilatation of the ducts, and a mass within the gland. RESULTS: Of the 908 patients who underwent thyroid ultrasonography, salivary gland abnormalities were detected in 36 (4.0%) patients. Of the 36 patients with abnormal ultrasonographic findings, 22 underwent further examination. Of the 22 patients, 16 received definitive diagnoses of salivary gland diseases. Salivary gland disorders were considered to be absent in patients with only heterogeneity of the salivary glands observed on ultrasonography. Salivary gland disorders in all patients with further abnormal ultrasonographic findings such as atrophy/swelling, unclear boundary, or hypervascularity in addition to internal heterogeneity were confirmed by further blood examinations and imaging studies. We were able to detect autoimmune sialadenitis such as Sjögren’s syndrome and IgG4-related sialadenitis by ultrasonography in patients without obvious symptoms. CONCLUSION: Salivary gland screening during thyroid ultrasonography revealed abnormal findings including Sjögren’s syndrome and IgG4-related sialadenitis in about 4% of the patients. Thus, ultrasonography may also be useful for early detection of autoimmune diseases of salivary glands.